Pengaruh Orientasi Pasar dan Jaringan Terhadap Kinerja Usaha Industri Makanan Oleh-Oleh - Lani Melani; Marina Marina (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the impact of market orientation and networking on business performance in the souvenir food industry. The research was conducted using a quantitative approach by distributing questionnaires to 40 respondents. Data analysis included normality tests, linear regression analysis, and the coefficient of determination to determine the relationship between variables. The results showed that market orientation and networking significantly affect business performance, with a coefficient of determination of 70%. Market orientation had a regression coefficient of 0.50 and networking had a regression coefficient of 0.45, both significant at p < 0.05.